Development of carbonaceous tin-based solder composite achieving unprecedented joint performance - Hawi, Sara; Gharavian, Somayeh; Burda, Marek; Goel, Saurav; Lotfan, Saeid; Khaleque, Tasnuva; Yazdani Nezhad, Hamed (Springer, 2021)
Weight reduction and improved strength are two common engineering goals in the joining sector to benefit transport, aerospace, and nuclear industries amongst others. Here, in this paper, we show that the suitable addition of carbon nanomaterials to a tin-based solder material matrix (C-Solder® supplied by Cametics Ltd.) results in two-fold strength of soldered composite joints. Single-lap shear joint experiments were conducted on soldered aluminium alloy (6082 T6) substrates. The soldering material was reinforced in different mix ratios by carbon black, graphene, and single-walled carbon nanotubes (SWCNT) and benchmarked against the pristine C-solder®. The material characterisation was performed using Vickers micro-indentation, differential scanning calorimetry and nano-indentation, whereas functional testing involved mechanical shear tests using single-lap aluminium soldered joints and creep tests. The hardness was observed to improve in all cases except for the 0.01 wt.% graphene reinforced solders, with 5% and 4% improvements in 0.05 carbon black and SWCNT reinforced solders, respectively. The maximum creep indentation was noted to improve for all solder categories with maximum 11% and 8% improvements in 0.05 wt.% carbon black and SWCNT reinforced ones. In general, the 0.05 wt.% nanomaterial reinforced solders promoted progressive cohesion failure in the joints as opposed to instantaneous fully de-bonded failure observed in pristine soldered joints, which suggests potential application in high-performance structures where no service load induced adhesion failure is permissible (e.g. aerospace assemblies). The novel innovation developed here will pave the way to achieving high-performance solder joining without carrying out extensive surface preparations.
Keywords: Carbon black; Graphene; Single-walled carbon nanotubes; Tin solder; Single-lap joint